The Importance of Managing Organisation’s Culture for Successful Mergers and Acquisitions - Sirajuddin, Seema (2010)
The complexities of international mergers is compounded by the strong differences in culture across organisation, which is one of the major reasons for the failure of most mergers and acquisitions. These cultural differences fail to produce any benefit arising from the consolidation process to the shareholders and are responsible for actually destroying the overall value of the organisation.